2021
DOI: 10.1186/s12978-021-01160-5
|View full text |Cite
|
Sign up to set email alerts
|

A cross-country qualitative study on contraceptive method mix: contraceptive decisionmaking among youth

Abstract: Background Youth ages 15 to 24, who comprise a large portion of sub-Saharan Africa, face a higher burden of unmet contraceptive need than adults. Despite increased international and national commitments to improving young people’s access to contraception, significant barriers impede their access to a full range of methods. To further explore these barriers among youth in Kenya, Nigeria, and Uganda, we conducted a qualitative study to capture the challenges that affect contraceptive method decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
0
23
1
Order By: Relevance
“…Youth had a marginally higher mean score on the information exchange metric largely due to young abortion clients more often being told about a barrier method for protection against STIs compared to non-youth clients. Although our study did not find any discernable difference between youth and non-youth, there is strong evidence in LMIC that demonstrates that young people, in particular adolescents, have limited knowledge of contraceptive methods [38]. Youth often have misconceptions about the side effects of contraceptives on their health and future fertility [39][40][41] and poor understanding of how contraceptives work and how they should be used [39,42].…”
Section: Discussioncontrasting
confidence: 72%
“…Youth had a marginally higher mean score on the information exchange metric largely due to young abortion clients more often being told about a barrier method for protection against STIs compared to non-youth clients. Although our study did not find any discernable difference between youth and non-youth, there is strong evidence in LMIC that demonstrates that young people, in particular adolescents, have limited knowledge of contraceptive methods [38]. Youth often have misconceptions about the side effects of contraceptives on their health and future fertility [39][40][41] and poor understanding of how contraceptives work and how they should be used [39,42].…”
Section: Discussioncontrasting
confidence: 72%
“…The decision to begin their contraceptive journey with condoms was influenced by several factors, but overwhelmingly the most common influences were related to the strong desire for a method that protected against both pregnancy and STIs, easy accessibility and low cost at pharmacies and shops, and a lack of knowledge about other methods. Use of condoms may be driven, in part, by wider social acceptability of young people using condoms which is rooted in the desire for a method that is used only when needed (coital dependent), not perceived to impact future fertility, as well as the appreciation of the dual protection they provide ( 10 , 15 , 17 ). Our study found that young women learn about condoms from a variety of sources, including teachers, peers, their partner and parents; this differs from the paper from Ouma et al which found that most young people learn about methods from peers and the internet ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Use of condoms may be driven, in part, by wider social acceptability of young people using condoms which is rooted in the desire for a method that is used only when needed (coital dependent), not perceived to impact future fertility, as well as the appreciation of the dual protection they provide ( 10 , 15 , 17 ). Our study found that young women learn about condoms from a variety of sources, including teachers, peers, their partner and parents; this differs from the paper from Ouma et al which found that most young people learn about methods from peers and the internet ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Pharmacies and drug shops are often preferred because of privacy concerns, convenience, fast service, and perceived youth-friendliness. 9 , 10 , 11 In a mixed-methods study in Kenya, young people identified pharmacies as a preferred option that afforded privacy without the prohibitive costs of private facilities; many young people were willing to pay more for private pharmacy services to access high-quality, private care, citing pharmacies’ consistent pricing as an added benefit. 10…”
Section: Introductionmentioning
confidence: 99%